1987
DOI: 10.1111/j.1476-5381.1987.tb11249.x
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of co‐carcinogenic phorbol esters and a synthetic diacylglycerol on human neutrophil chemokinesis and granular enzyme secretion

Abstract: The effects of two co‐carcinogenic phorbol esters (phorbol myristate acetate (PMA) and phorbol dibutyrate (PDBu)) and a synthetic diacylglycerol (OAG, 1‐oleoyl‐2‐acetyl‐glycerol), which all stimulate protein kinase C, were compared with two inactive phorbol compounds (4α‐phorbol and 4α‐phorbol didecanoate (4α‐PDD)) on three functional properties of stimulated human polymorphonuclear leukocytes (PMNs): release of granular enzymes lysozyme and β‐glucuronidase, chemokinesis, and changes in cytoplasmic free calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Another plausible explanation is that the aforementioned study used PDBu, whereas we utilized the PKC activator PMA. PMA and PDBu are phorbol esters that mimic DAG, the natural activator of PKC; however, differences in pharmacological properties of PDBu and PMA were reported, and the results showed that PMA is a more potent PKC activator (30). We should also consider that there are 11 different PKC isoforms, classified into 3 major groups (18,23,28,29).…”
Section: Discussionmentioning
confidence: 95%
“…Another plausible explanation is that the aforementioned study used PDBu, whereas we utilized the PKC activator PMA. PMA and PDBu are phorbol esters that mimic DAG, the natural activator of PKC; however, differences in pharmacological properties of PDBu and PMA were reported, and the results showed that PMA is a more potent PKC activator (30). We should also consider that there are 11 different PKC isoforms, classified into 3 major groups (18,23,28,29).…”
Section: Discussionmentioning
confidence: 95%
“…27. Moreover, DAGK inhibition or treatment with synthetic DAG species leads to alterations in normal PMN motility (35)(36)(37). Therefore, defective DAGK expression provides a potential molecular basis that may explain disparate functional responses in PMN from patients with LAP, namely, agonist-specific reduced motility and enhanced production of superoxide anions and related reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the fMet-Leu-Phe-induced change of neutrophil shape to a polarized, locomotory cell shape in suspension was counteracted by the addition of PMA [21]. The PMA concentrations that efficiently decreased neutrophil locomotion and shape changes are found to be in the nanomolar range (this study) [21,30,31]. In this context, it is important to recall that in order to activate secretion of superoxide anions from the NADPH-oxidase, at least 10 times higher PMA concentrations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…PKC activation by phorbol esters, like PMA, is known to inhibit random locomotion of neutrophils (this study) [21] and of Walker carcinosarcoma cells [30], as well as inhibiting neutrophil chemokinesis stimulated by several agonists (i.e., fMet-Leu-Phe, leukotriene B 4 , C5a, platelet-activating factor) [31]. Also, the fMet-Leu-Phe-induced change of neutrophil shape to a polarized, locomotory cell shape in suspension was counteracted by the addition of PMA [21].…”
Section: Discussionmentioning
confidence: 99%